Pengembangan Bahan Ajar Matematika Berbasis Pembelajaran Mendalam pada Siswa Kelas VII SMPN 3 Sibulue - Aulia Firman; Usman Mulbar (Proximal: Jurnal Penelitian Matematika dan Pendidikan Matematika, 2026)
This study is motivated by the low level of students’ mathematical conceptual understanding, which is caused by learning that still focuses on memorization and procedural steps without deep conceptual meaning. This study aims to develop mathematics teaching materials based on deep learning for seventh-grade students at SMPN 3 Sibulue. This research uses a Research and Development (R&D) method with the ADDIE model, which consists of analysis, design, development, implementation, and evaluation stages. The research subjects were seventh-grade students of SMPN 3 Sibulue. Data collection techniques included observation, questionnaires, and learning outcome tests. The data were analyzed quantitatively and qualitatively to determine the validity, practicality, and effectiveness of the teaching materials. The expected result of this study is the development of deep learning-based mathematics teaching materials that meet the criteria of being valid, practical, and effective in supporting meaningful learning. Therefore, the developed teaching materials are expected to become an alternative in improving the quality of mathematics learning, especially in terms of students’ mathematical conceptual understanding.